Pengaruh Citra Merek, Kualitas Produk, dan Kepercayaan Terhadap Keputusan Pembelian pada Blibli di Kota Batam - Nurmala Sari Hasibuan; Winda Evyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to explore the extent to which brand image, product quality, and trust influence purchasing decisions for Pixy two-way cake through the Blibli platform in Batam City. The approach used is quantitative descriptive, involving 100 consumers who previously purchased Pixy two-way cake on Blibli, selected through purposive sampling with Lemeshow calculation guidelines to ensure sample representativeness. Data collection was conducted using a questionnaire, then analyzed through validity and reliability tests, classical assumption evaluation, multiple linear regression, and hypothesis testing using t-tests and F-tests. The results of the regression analysis indicate that brand image has a 24.7% influence on purchasing decisions, product quality contributes 34.0%, and trust plays a role of 29.2%. Furthermore, the coefficient of determination (R²) shows that these three variables collectively explain 74.0% of the variation in purchasing decisions. The t-test and F-test confirm that the influence of each variable is significant and positive, both partially and simultaneously, on consumer purchasing decisions at Blibli in Batam City.